Hepatotoxic Restorative Potential of Whitfieldia Lateritia Leaf Decoction and Vitali Supplement on Phenylhydrazine-Induced Anemic Cockerels (Global Journal of Science Frontier Research, 2020)
Abstract not found
Keywords: phytochemical; decoction; anaemia; feed conversion; whitfieldia lateritia